A comparison of autologous transplantation of retinal pigment epithelium (RPE) monolayer sheet graft with RPE–Bruch's membrane complex graft in neovascular age‐related macular degeneration. Issue 6 (6th August 2016) - Lu, Yao; Han, Liang; Wang, Changguan; Dou, Hongliang; Feng, Xuefeng; Hu, Yuntao; Feng, Kang; Wang, Xin; Ma, Zhizhong
Abstract: Purpose: To compare the outcome after choroidal neovascular (CNV) membrane excision and retinal pigment epithelium (RPE) transplantation and make further evaluation of two types of RPE grafts on the visual function in patients with neovascular age‐related macular degeneration (AMD), complicated by massive subretinal haemorrhage. Methods: We retrospectively reviewed 80 patients who underwent CNV membrane excision with or without RPE transplantation. Two types of RPE grafts were adopted, RPE–Bruch's membrane complex graft (subgroup 1) and RPE monolayer sheet graft (subgroup 2). Outcome measures included pre‐ and postoperative visual acuity score (VAS), clinical findings, complications and recurrence rates. Results: The mean VAS [Early Treatment of Diabetic Retinopathy Study (ETDRS)] in the CNV membrane excision group was 11.06 ± 18.28 at baseline and 14.41 ± 16.86 at follow‐up (p = 0.12) in a mean follow‐up period of 24.35 ± 9.31 months. While in subgroup 1, VAS increased from 22.62 ± 23.72 to 35.50 ± 24.46 (p = 0.02) in a mean period of 20.63 ± 6.25 months. The percentage of visual acuity (VA) improvement (at least two or more lines changed) in subgroup 1 is 62.5%, which is significantly higher than that in CNV excision group (23.5%), p = 0.02. In subgroup 2, VAS increased from 16.61 ± 27.98 to 29.16 ± 23.80 (p = 0.02) in a mean period of 21.72 ± 11.09 months. The percentage of VA improvement in subgroup 2 is 58.0%, which is also significantly higher than that in CNV excision group (23.5%), p = 0.02. Postoperative VA elevation was comparable between the two subgroups (p = 0.05). Complications including retinal detachment, proliferative vitreal retinopathy and CNV recurrence occurred in both techniques. Central fixation stability was observed in eight eyes in subgroup 1 and five eyes in subgroup 2. Conclusions: The autologous RPE transplantation can increase the vision of patients with haemorrhagic AMD. Two types of autologous RPE grafts were both effective and comparable in restoring visual function and central fixation stability.